2013
DOI: 10.3892/mmr.2013.1399
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside promotes bone marrow mesenchymal stem cell proliferation in rats

Abstract: The aim of this study was to explore the mechanism underlying the promotive effect of morroniside on rat mesenchymal stem cell (RMSC) proliferation and to provide an experimental basis for the development of potential new drugs. RMSCs were obtained from the bone marrow of Sprague-Dawley rats aged 3-4 months. The proliferation of primary and subcultured RMSCs in the high‑, medium‑ and low‑concentration morroniside intervention and blank control groups was observed using light microscopy. Cell proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…So we expected that one of the two components of EE-rbSWH may playing a mainly role on promoting osteoblasts differentiation, or the mutually coordinated actions of the two components. Morroniside, which was the highest content Iridoids compound in EE-rbSWH (more than 50%) (Han et al, 2013a(Han et al, , 2013b, also had the function of promoting osteogenic differentiation (Hu et al, 2013;Li et al, 2010). So we speculated it may be the main active ingredient of EE-rbSWH in promoting fracture healing.…”
Section: Discussionmentioning
confidence: 86%
“…So we expected that one of the two components of EE-rbSWH may playing a mainly role on promoting osteoblasts differentiation, or the mutually coordinated actions of the two components. Morroniside, which was the highest content Iridoids compound in EE-rbSWH (more than 50%) (Han et al, 2013a(Han et al, , 2013b, also had the function of promoting osteogenic differentiation (Hu et al, 2013;Li et al, 2010). So we speculated it may be the main active ingredient of EE-rbSWH in promoting fracture healing.…”
Section: Discussionmentioning
confidence: 86%
“…The specific mechanism of morroniside promoting RMSC proliferation has yet to be clarified, but the process may occur by secreted factors, cell-to-cell interactions, and/or interactions between cellular adhesion molecules and extracellular matrices. 35 Manyu Li et al also found that morroniside isolated from Liuwei Dihuang pills may directly promote the differentiation and inhibit the apoptosis of MC3T3-E1 cells. The anti-osteoporotic mechanisms in MC3T3-E1 cells are likely to improve the activity of alkaline phosphatase, increase the contents of collagen type I and osteocalcin, downregulate the mRNA expression of caspase-3 and capase-9, and upregulated the mRNA expression of bcl-2.…”
Section: Treating Osteoarthritismentioning
confidence: 99%
“…It also prevents apoptosis of cardiomyocytes induced by high glucose [ 180 ]. In the skeletal system, morroniside promotes osteoblast proliferation [ 181 ] and formation through PI3K/Akt/mTOR signaling both in vitro and in vivo [ 182 ]. Morroniside activates Akt and extracellular signal-regulated kinase (ERK) to promote cartilage cell survival and matrix synthesis [ 183 ].…”
Section: Monoterpenesmentioning
confidence: 99%